A phylogenomic tree of fungi: evolutionary relationships among Calonectria ilicicola and 586 fungal mitochondrial genomes - Yunpeng Gai; Ruqian Pan; Xujian Peng (Mitochondrial DNA. Part B. Resources, 2020)
The mitochondrial genomes have the potential to be ‘molecular clock’ due to its high mutation rate and low DNA recombination rate. Here, we sequenced the complete mitochondrial genome of three strains of Calonectria ilicicola (anamorph Cylindrocladium parasiticum) isolated from diseased peanut showing symptoms of Cylindrocladium black rot (CBR) and two C. ilicicola strains isolated from diseased soybean showing symptoms of Red crown rot (RCR). The complete mitogenome of C. ilicicola ranged from 41,187 bp to 64,421 bp in length, 22–34 protein-coding genes, 19–20 tRNA genes, 2 rRNA genes, and a control region. Besides, we used a phylogenomic approach to infer evolutionary relationships among 591 mitochondrial genomes that span the diversity of 294 fungal species, including C. ilicicola. Our results underline the potential importance of mitochondrial genomes in comparative genomic analyses and provide a robust evolutionary insight across the tree of life.